Teaching Careers: Exploring Links Between Well-Being, Burnout, Self-Efficacy and Praxis Shock - Ballantyne, Julie; Retell, James (Frontiers in Psychology, 2020)
Burnout and attrition are issues facing many professions. In a bid to better understand this phenomenon and ways to address it, this paper explores experiences of praxis shock, well-being, burnout and self-efficacy during teachers’ careers. Regression and mediation analyses of 836 responses to a questionnaire reveal that praxis shock may occur at multiple points in a music teachers' career. Findings reveal that praxis shock predicts patterns of reported burnout, well-being and self-efficacy. This impacts on the development of productive professional identities, career satisfaction and success. Evidence is presented regarding praxis shock and its impact across a teaching career.